Consistency paradox revisited. A procedure for estimating interindividual consistency independently from the measure - Hernández, José Manuel; Rubio, Victor J.; Santacreu, José; Revuelta, Javier (Análisis y Modificación de Conducta, 2025)
Mischel (1968) argued against the idea of a general consistency of human beings.